The Role of Marketing Management for Society - Yoeyong Rahsel; Miswan Gumanti; Ayu Lidia; Andino Maseleno (Siber Journal of Advanced Multidisciplinary, 2026)
Marketing is a crucial factor in a company's development. Effective marketing is achieved through product, price, place, and promotion. Lack of understanding of changing or dynamic consumer tastes, as well as ineffective marketing strategies, will negatively impact target market achievement. The objective of this research is to understand the role of marketing in society. The research method employed is a literature study. In accordance with the research focus, various literature sources, books, and other information sources were obtained to obtain data on the role of marketing in society and organizations. From a product perspective, the desired product is one that meets their needs, is high-quality, has an attractive design, is environmentally friendly, and is easily remembered. From a price perspective, the public desires a price that matches the quality, is affordable for all levels of society, and is competitive. From a place perspective, the public wants the product to be purchased to be easily available, accessible, and has a limited reach. From a promotional perspective, the public desires marketing to be carried out through methods such as door-to-door promotion, online marketing, and personal selling.